Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.iecr.0c04286
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Optimization of Microgel Synthesis in the μm Size Range

Abstract: Microgels are functional polymer colloids with diverse applications, for example, in medicine, engineering, or agriculture. Some applications require large microgels in the size range of μm, which could previously only be synthesized using microfluidics or a synthesis procedure involving a fed-batch reaction with a temperature ramp. We use dynamic optimization to determine a simpler synthesis recipe that allows us to synthesize microgels in the μm range using a batch procedure. First, a sensitivity analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 40 publications
(87 reference statements)
1
9
0
Order By: Relevance
“…The later increase in particle size and D h was mainly due to the fierce collision, entanglement, and aggregation among the concentrated active chains, generating large gel particles. Our results demonstrated that the effects of the cross-linker and initiator on microgel size were consistent with that of the traditional batch reactor. …”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The later increase in particle size and D h was mainly due to the fierce collision, entanglement, and aggregation among the concentrated active chains, generating large gel particles. Our results demonstrated that the effects of the cross-linker and initiator on microgel size were consistent with that of the traditional batch reactor. …”
Section: Resultssupporting
confidence: 80%
“…In comparison, a conventional STR was used to synthesize PNIPAM microgels under the same reaction conditions as in the RPB. It took 6 h to react completely, as reported before . The results are shown in Table .…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The efficiency of the initiator decomposition is set to 50%. 19 The kinetics of the propagation reactions depend only on the radical at the terminal end of the chain, and propagation reactions contribute majorly to the enthalpy release. Termination only occurs due to disproportionation, and the kinetics of termination reactions do not depend on the terminal end of the active radical chains, as they are mostly diffusion limited.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The model contains 21 parameters. Out of the 21 parameters, we adopt three propagation rate constant values, three polymerization enthalpy values, and the initiator efficiency value from our previous studies. , Using transition state theory and quantum chemical calculations, we compute 12 out of 21 parameters, namely, the propagation rate constants and polymerization enthalpies of GMA/VCL and GMA/BIS systems in an aqueous solution. We include all quantum chemically computed polymerization enthalpies and the model’s four least impactful propagation rate constants into the final model.…”
Section: Introductionmentioning
confidence: 99%